2014
DOI: 10.1039/c4sc01401d
|View full text |Cite
|
Sign up to set email alerts
|

Controlling selectivity in the reductive activation of CO2 by mixed sandwich uranium(iii) complexes

Abstract: The uranium complexes [U(η8-C8H6(1,4-SiMe3)2)(η5-CpMe4R)] can be tuned to selectively reduce CO2, giving U(iv) complexes incorporating bridging oxo, carbonate, or oxalate groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 64 publications
3
68
0
2
Order By: Relevance
“…Complex 6 shows an irreversible reduction wave at −2.19 V vs FeCp2 +/0 ( Figure S4) which is in excellent agreement with the quasi-reversible process at −2.18 V vs FeCp2 +/0 seen in 3 and is assigned to the U IV /U III couple in this system. This value is similar to other U IV /U III redox couples found in other U III systems studied by us and others 10,21 and is consistent with a strongly reducing metal center. Further supporting this assignment is the observation of a single quasi-reversible reduction process at −2.19 V vs FeCp2 +/0 in the dinuclear U(IV) complex, 4 ( Figure S2).…”
Section: Scheme 5 Synthesis Of [U(cp*)(p-me2bp)i] (6)supporting
confidence: 77%
See 1 more Smart Citation
“…Complex 6 shows an irreversible reduction wave at −2.19 V vs FeCp2 +/0 ( Figure S4) which is in excellent agreement with the quasi-reversible process at −2.18 V vs FeCp2 +/0 seen in 3 and is assigned to the U IV /U III couple in this system. This value is similar to other U IV /U III redox couples found in other U III systems studied by us and others 10,21 and is consistent with a strongly reducing metal center. Further supporting this assignment is the observation of a single quasi-reversible reduction process at −2.19 V vs FeCp2 +/0 in the dinuclear U(IV) complex, 4 ( Figure S2).…”
Section: Scheme 5 Synthesis Of [U(cp*)(p-me2bp)i] (6)supporting
confidence: 77%
“…solvent-free) has recently been reported as a potentially high yielding and selective approach to exploring subsequent reduction chemistry. 19 Recent work from our own laboratory has used supercritical CO2 to promote the exclusive formation of U(IV) bridging carbonate complexes, 10 and this approach was used to investigate the reductive activation of CO2 by 3 (Scheme 3). The reaction of solid 3 in supercritical CO2 resulted in an immediate color change from green-black to orange, and the resultant orange powder contained only one major product (>96% by 1 H NMR spectroscopy), confirming the highly selective nature of the reaction.…”
Section: Carbon Dioxide Activationmentioning
confidence: 99%
“…This C-S bond formation is reminiscent of the C-O bond formation reported by Castro et al in carbonate formation in U III and Sm II chemistry. [30][31][32][33] How-ever, in the latter, after C-O bond formation, C-O bond cleavage occurred to form a CO molecule. Interestingly, in this study (Figure 3), C-S bond breaking is not observed, which strengthens the argument of the lack of stability of the CS molecule.…”
Section: Resultsmentioning
confidence: 99%
“…[164] Electrochemical studies on both the uranium(III) complexes and the dimeric uranium(IV) CO 2 reduction products have been carried out and all exhibited quasireversible redox processes. In particular, the similarities in the U(III)/U(IV) redox couples suggested that the selectivity in the outcome of CO 2 reductive activation by these complexes is steric in origin rather than electronic.…”
Section: Other Organolanthanide-catalyzed Reactionsmentioning
confidence: 99%
“…Three possible mechanisms have been identified, as illustrated in Sm III -CO 2 -Sm III Cp * 2 was also observed and was found to react with a second molecule of CO 2 to yield the corresponding bimetallic oxalate complex via C-C coupling (mechanism M3). [164] 2LU III + CO 2 LU IV -CO 2 The CASSCF methodology was used to calculate the ground state electron densities of a series of seven actinocenes, AnCOT, (An = Th-Cm, COT = η 8 -C 8 H 8 ). Topological analysis revealed increased values of the electron density at the An-C bond for An = Pa-Pu, suggesting enhanced covalent character in metal-ligand bonding for these complexes.…”
Section: Other Organolanthanide-catalyzed Reactionsmentioning
confidence: 99%